2019
DOI: 10.1108/nbri-08-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

Study of the influence of employee safety voice on workplace safety level of small- and medium-sized enterprises

Abstract: Purpose To improve unsafe workplace of Chinese SMEs, this paper aims to use the multi-agent simulation experiment to reveal the relationship between employees’ safety voice and safety level of enterprises. Design/methodology/approach Through simulation of employees’ safety voice activities, enterprises’ production activities, enterprises’ safety activities, an experiment platform is built. The experiment introduces external variable of labor resource and sets four experimental situations considering whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 61 publications
1
9
0
2
Order By: Relevance
“…In a survey of bus drivers, Herachwati, Sulistiawan, and Alfirdaus (2018) found that safety voice negatively affected employee satisfaction with the company. The results of the experiment by Zhang, Mei, and Liu (2019) showed that safety voice could significantly enhance the safety performance of companies when there is a labor shortage or when employees have high values. Mathisen, Tjora, and Bergh (2022) analyzed questionnaire data from oil workers and discovered that safety voice significantly inhibited safety risk and personal injury.…”
Section: Conceptual Definition and Connotation Of Safety Voicementioning
confidence: 99%
“…In a survey of bus drivers, Herachwati, Sulistiawan, and Alfirdaus (2018) found that safety voice negatively affected employee satisfaction with the company. The results of the experiment by Zhang, Mei, and Liu (2019) showed that safety voice could significantly enhance the safety performance of companies when there is a labor shortage or when employees have high values. Mathisen, Tjora, and Bergh (2022) analyzed questionnaire data from oil workers and discovered that safety voice significantly inhibited safety risk and personal injury.…”
Section: Conceptual Definition and Connotation Of Safety Voicementioning
confidence: 99%
“…Among the former are consumers (Jenkins, 2006;Niehm et al, 2007;Perrini et al, 2007;Stubblefield Loucks et al, 2010;Youssef et al, 2018), large companies, public administrations, and the media. The latter agents include the entrepreneurs' values and search for the best possible results in terms of workplace climate, productivity, innovation, and management (Adams et al, 2016;Machová et al, 2016;Zhang et al, 2019). Consumers expect companies to offer minimum levels of quality and to commit to ethical conduct.…”
Section: Recent Issues In Economic Developmentmentioning
confidence: 99%
“…However, the current safety situation is still in an alarming state, in particular, the frequency of serious accidents and serious hazards. Safety accidents are harmful to organizations, so taking effective measures to reduce the accident rate is the top priority for an enterprise's development [1]. Safety voice is considered to be the antecedent that helps avoid accidents [2][3][4], and the importance of safety voice in organizations is becoming more and more prominent.…”
Section: Introductionmentioning
confidence: 99%